The Analysis of Policy Directions of Geography Teacher’s Professional Competence in Mastering Natural Disaster Adaptation and Mitigation Materials in State Senior High Schools in Lubuk Linggau City - Sari, Desy Novita (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research was based on the result of researher’s observation in state senior high schools in Lubuk Linggau City which found that Geography teachers’ professional competence was low. The purpose of this research was to obtain policy directions of Geography teacher’s professional competence in mastering natural disaster adaptation and mitigation materials in state senior high scools in Lubuk Linggau City regarding: (1) Geography Teacher’s professional competence, (2) Problems faced by Geography Teacher, and (3) Efforts to improve Geography teacher’s professional competence.This research was a descriptive mixed method research. The sampling technique used was purposive sample, a way to take a sample based on certain consideration.Population of the research was 14 Geography teachers who were teaching in state senior high schools in Lubuk Linggau City. Instruments used were interviews (on teachers, schools principals, education authorities of Lubuk Linggau City), questionnaire and obervation sheet. The questionnaire used likert’s five scale and it was considered to be valid and reliable based on the data from the pilot test of the questionnaire which was analyzed by SPSS version 16. To analyze the data, the researcher calculated the mean value of item response. The result of the study showed that the policy directions of Geography teacher’s professional competence in mastering natural disaster adaptation and mitigation in state senior high schools in Lubuk Linggau City were (1) Geography teacher’s mastery of Syllabus, Lesson Plan, and teaching material, (2) Reactivating MGMP (the forum of subject teachers) activity especially for Geography teachers in Lubuk Linggau City, (3) Improving Geography teacher’s motivation through science and technology training program, (4)Supplying enough facilities to support teaching and learning process, and (5) Improving the professional competence of Geography teachers through coaching by supervisors and principals. The result of this research suggested five policy direction priorities. These priorities could be suggested to head of the education office and other related parties in order to improve Geograpy teacher’s professional competence in state senior high schools in Lubuk Linggau City.